THE PHILOSOPHICAL MEANING OF WAYANG DAPURA IN SUNAN KUDUS FIGURE - Javian Inggit Restianto; Kundharu Saddhono; Djoko Sulaksono (IBDA` : Jurnal Kajian Islam dan Budaya, 2020)
This writing is about the philosophy of Wayang Dupara, The Sunan Kudus. The body structure of Sunan Kudus is categorized as the body structure of Wayang Katongan. The research is assessed through descrip- tively qualitative method by uncovering the outer (physical) and inner (psyche) structure. The top accessories, the kuluk songkok and the garuda mungkur, are also included in the assessed physical and psyche struc- ture. The red colored make-up, kadelen’s eye, and walimiring nose are also examined. The puppet (wayang) is worn a robe with number of ac- cessories, like: rimong, tasbih, cundrik. The puppet’s foot part is worn a traditional foot wear, namely canela or selop. The result for both outer and inner figure is related to Sunan Kudus in Islamic Javanese perspec- tive as the person who had an important role in religion, intellect, reign and economic area